Work Value Transmission From Parents to Children: Early Socialization and Delayed Activation. Issue 1 (February 2020) - Johnson, Monica Kirkpatrick; Mortimer, Jeylan T.; Heckhausen, Jutta
This study examines the transmission of work values from parents to children between mid-adolescence and early midlife. The authors propose that work-related values are transmitted from parents to children in two sequential and complementary processes stretched across adolescence and early adulthood. The first process of work value exposure and reception in the family context is captured by the socialization model. The second process is one of delayed value activation, long after initial socialization, when the young adult offspring engages with the demands and vicissitudes of their own emerging careers. The authors find evidence for family socialization in adolescence and also support for the delayed activation model during adulthood. Although parental values were measured more than two decades earlier, the authors find the strongest associations of parent and child values when the offspring were in their late 30s. In addition, parent–child value similarity is heightened when adult children navigate career uncertainty and change, consistent with a delayed activation process.